Sale-based estimation of pharmaceutical concentrations and associated environmental risk in the Japanese wastewater system - Kai He; Alistair G. Borthwick; Lin, Yingchao; Yuening Li; Fu, Jie; Yongjie Wong; Liu, Wen (Environment International, 2020)
Information on sales and emission of selected pharmaceuticals were used to predict their concentrations in Japanese wastewater influent through a >300 of pharmaceuticals data sink. A combined wastewater-based epidemiology and environmental risk analysis follow was established. By comparing predicted environmental concentrations (PECs) of pharmaceuticals in wastewater influent against measured environmental concentrations (MECs) reported in previous studies, it was found that the model gave accurate results for 17 pharmaceuticals (0.5 < PEC/MEC < 2), and acceptable results for 32 out of 40 pharmaceuticals (0.1 < PEC/MEC < 10). Although the majority of pharmaceuticals considered in the model were antibiotics and analgesics, pranlukast, a receptor antagonist, was predicted to have the highest concentration in wastewater influent. With regard to the composition of wastewater effluent, the Estimation Program Interface (EPI) suite was used to predict pharmaceutical removal through activated sludge treatment. Although the performance of the EPI suite was variable in terms of accurate prediction of the removal of different pharmaceuticals, it could be an efficient tool in practice for predicting removal under extreme scenarios. By using the EPI suite with input data on PEC in the wastewater influent, the PEC values of pharmaceuticals in wastewater effluent were predicted. The concentrations of 26 pharmaceuticals were relatively high (>1 μg/L), and the PECs of 6 pharmaceuticals were extremely high (>10 μg/L) in wastewater effluent, which could be attributed to their high usage rates by consumers and poor removal rates in wastewater treatment plants (WWTPs). Furthermore, environmental risk assessment (ERA) was carried out by calculating the ratio of predicted no effect concentration (PNEC) to PEC of different pharmaceuticals, and it was found that 9 pharmaceuticals were likely to have high toxicity, and 54 pharmaceuticals were likely to have potential toxicity. It is recommended that this is further investigated in detail. The priority screening and environmental risk assessment results on pharmaceuticals can provide reliable basis for policy-making and environmental management.
Keywords: Environmental risk assessment; EPI suite; Pharmaceuticals; Predicted environmental concentrations; Wastewater system